2016
DOI: 10.1242/dev.128900
|View full text |Cite
|
Sign up to set email alerts
|

Split top: A maternal cathepsin B that regulates dorsoventral patterning and morphogenesis

Abstract: The vertebrate embryonic dorsoventral axis is established and patterned by Wnt and bone morphogenetic protein (BMP) signaling pathways, respectively. Whereas Wnt signaling establishes the dorsal side of the embryo and induces the dorsal organizer, a BMP signaling gradient patterns tissues along the dorsoventral axis. Early Wnt signaling is provided maternally, whereas BMP ligand expression in the zebrafish is zygotic, but regulated by maternal factors. Concomitant with BMP activity patterning dorsoventral axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 103 publications
5
10
0
Order By: Relevance
“…Similar to DMP, TDCIPP exposure resulted in a concentration-dependent increase in the severity of dorsalization, suggesting that TDCIPP exposure results in inhibition of normal BMP signaling and downstream effects on dorsoventral patterning. Moreover, the presence of split yolk phenotypes (while rare) also supports the conclusion that TDCIPP interferes with BMP-related pathways, as these phenotypes are characteristic of zebrafish split top mutants deficient in BMP signaling ( Langdon et al, 2016 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar to DMP, TDCIPP exposure resulted in a concentration-dependent increase in the severity of dorsalization, suggesting that TDCIPP exposure results in inhibition of normal BMP signaling and downstream effects on dorsoventral patterning. Moreover, the presence of split yolk phenotypes (while rare) also supports the conclusion that TDCIPP interferes with BMP-related pathways, as these phenotypes are characteristic of zebrafish split top mutants deficient in BMP signaling ( Langdon et al, 2016 ).…”
Section: Discussionsupporting
confidence: 52%
“…Within the current study, we discovered that, while the majority of epiboly-delayed embryos appear normal at 24 hpf, 76% of epiboly-arrested embryos resulted in dorsalized phenotypes, suggesting that epiboly arrest—but not epiboly delay—at 6 hpf leads to dorsalization by 24 hpf. Previous studies have shown that mutations in early zygotic genes lead to epiboly defects, disruptions in dorsoventral patterning, and severe deformities in surviving embryos ( Haffter et al, 1996 ; Kane et al, 1996 ; Kane, McFarland & Warga, 2005 ; Langdon et al, 2016 ). Therefore, the link between epiboly arrest and dorsalization observed following TDCIPP exposure suggests that TDCIPP may interfere with the normal function of early zygotic gene products.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin D mediates early stages of perichondral ossification [ 68 ], and although myopathy was reported in zebrafish morphants no cartilage phenotypes were noted [ 69 ]. Cathepsin B is elevated in in vitro models of osteoarthritis [ 70 ] and promotes early embryonic patterning in zebrafish via BMP signaling, but no jaw phenotypes were noted in mutants [ 71 ]. Collectively, the absence of kif5Blof like phenotypes in these mutants suggests that Kif5B modulates cell maintenance during chondrogenesis by a mechanism that is distinct from these cathepsins.…”
Section: Discussionmentioning
confidence: 99%
“…General lysosomal enzymes, phosphatases and proteinases have been suggested to be involved in yolk protein degradation of eggs in various animals including avians, amphibians, fish, crustaceans and insects ( Perona & Vallejo, 1982 ; Lemanski & Aldoroty, 1977 ; Vogel & Gerster, 1997 ; Carnevali et al, 1999b ). Products of maternal cathepsin transcripts including cathepsin B & D are associated with oocyte development in the ovary, and their RNA is depleted during embryo development ( Carnevali et al, 2008 ; Follo et al, 2013 ; Fernandez et al, 2013 ; Langdon et al, 2016 ). It has been suggested that transcript level of cathepsin B & D can determine the quality of eggs and embryos in a pelagic fish species ( Palomino et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%